Discretion as a Factor in Corruption: A Case from Indonesia. (30th November 2022) - Kurniawan, Teguh
Abstract: This study asks whether legitimate exercise of discretion led to the charges of corruption brought against regional Indonesian heads by the Corruption Eradication Commission during 2004–2010. This question arises in the context of the findings from numerous studies that cite two main causes for Indonesian regional governments to indulge in budgetary corruption: lack of transparency, supervision, and accountability; and uncontrolled exercise of discretion. Some studies in the literature mention how discretion can lead to corruption if abused. Based on the opinions of various experts regarding the misuse of discretion, there is a need to examine corruption and its relation to discretion. This study's significance lies in the fact that corruption studies related to discretion are rare. Using a qualitative approach by studying court decision documents and conducting in-depth interviews with several informants, three well-publicized cases are examined. The results show that the charges of corruption could not be considered legitimate discretionary measures. Rather, regional heads acted in violation of clear laws and regulations, jointly or assisted by others, for their personal benefit and not for public interest. The heads simply exceeded their statutory authority. The results also confirm that absent or inadequate accountability encourages corruption.